2021
DOI: 10.1093/eurpub/ckab164.413
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of metabolic syndrome prevalence using four definitions – a case study from Finland

Abstract: Background Metabolic syndrome (MetS) is an increasing population health threat in Europe. Several MetS definitions are available. Our aim was to compare four different MetS definitions among Finnish adults, to assess their agreement and to evaluate the impact of the choice of the definition on the prevalence of MetS. Methods Data from FinHealth 2017, a cross-sectional population health survey, focusing on adults over 25 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Regarding the criterion established by the International Diabetes Federation (IDF) [ 46 ], despite having the same cutoff points for the components, whereas the JIS [ 23 ] considers at least three altered parameters among any of the five components, the IDF includes abdominal obesity as a mandatory component alongside two other altered parameters to define MetS. These differences contribute to the identification of a greater number of individuals with high waist circumference and MetS with the criteria established by JIS, as indicated by several studies in the literature [ 47 , 48 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the criterion established by the International Diabetes Federation (IDF) [ 46 ], despite having the same cutoff points for the components, whereas the JIS [ 23 ] considers at least three altered parameters among any of the five components, the IDF includes abdominal obesity as a mandatory component alongside two other altered parameters to define MetS. These differences contribute to the identification of a greater number of individuals with high waist circumference and MetS with the criteria established by JIS, as indicated by several studies in the literature [ 47 , 48 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the study by Subías-Perié et al, they found that the IDF definition and the JIS definition had the best agreement (k = 1.000). Meanwhile, the Finnish work by Haverinen et al (22) found that the IDF and JIS definitions had almost perfect agreement (k = 0.97), while the agreement between the ATPIII and JIS definitions was strong (k = 0.80).…”
Section: Concordance Of the Three Definitions Of Metsmentioning
confidence: 99%